(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2020)
The experiment was conducted to determine the effects of population densities of tilapia (Oreochromis niloticus) on the growth and production of tilapia in monoculture system. Fish population density was 80 fish per decimal under treatment-I, 160 fish per decimal under treatment-II and 320 fish per decimal under treatment-III. In the ponds under three treatments supplementary feed was not used. The average initial length and weight of the fry of tilapia was 4.48 cm and 0.067 g, respectively. The ponds were fertilized fortnightly with urea and TSP at the rates of 60 g, and 90 g per decimal, respectively. Mean survival rates of fish under treatment-I, treatment-II and treatment-III were 91.12%, 82.82% and 66.23%, respectively. The specific growth rates (SGR, % per day) of fish under treatment-I, treatment-II and treatment-III were 5.49%, 4.95% and 4.61%, respectively. The calculated net fish production of the ponds under treatment-I was 2.65 ton ha-1 yr-1 and that of the ponds under treatment-II was 2.55 ton ha-1 yr-1 and that of the ponds under treatment-III was 2.68 ton ha-1 yr-1. The net fish production under treatment-I and treatment-III were 2.65 ton ha-1 yr-1 and 2.68 ton ha-1 yr-1 higher than that of treatment-II, taking net fish production under treatment-I for 100%. According to survival rates and specific growth rates treatment-I is the best. So, the population density of 80 fish per decimal (under treatment-I) might be considered the best among the three treatments. Int. J. Agril. Res. Innov. Tech. 9(2): 76-83, December 2019